A hybrid KNN-MLP algorithm to diagnose bipolar disorder - Mohammad Ghasemi, Mozhgan; Khalili, Mehdi (Journal of Advanced Computer Science & Technology, 2014)
In this paper an attempt has been made to the other corner of the power of neural networks. According to the neural network in the diagnosis of diseases, we use neural network models for diagnosing bipolar disorder; bipolar disorder is the common disorder of depression mood. We have used two neural network models: MLP & KNN. With different percentages of the implementation of neural network models is discussed. And the error was calculated for each model. We can by using the MLP model achieve an error of 16% for the diagnosis of bipolar disorder.